PENCEGAHAN PERUSAKAN HUTAN BERBASIS MASYARAKAT ADAT DALIHAN NA TOLU DI TAPANULI SELATAN - Anwar Sadat Harahap; Ahmad Laut Hasibuan (Masalah-Masalah Hukum, 2019)
There are indigenous peoples who have their own traditional value in passing the prevention of forest destruction. Before the establishment of legislation on Preventing Forest Destruction in Indonesia, the indigenous people of Dalihan na Tolu have their own rules in preventing forest destruction. The customary law of Dalihan na Tolu has governed: the model of settlement of forest degradation disputes, the universal rules of indigenous peoples of Dalihan na Tolu on the prevention of forest destruction, the form of sanctions imposed on forest destruction parties, and the form of oversight in the implementation of the prevention of forest destruction.